Pedagogical environment, soft skills, and laboratory performance mediators of biology students achievement in technology-enabled metaliteracy - Mendoza, Cesar M. (College of Education, University of the Philippines Diliman, 2019)
To provide an alternative approach in the teaching and learning process of biology education and with the paucity of literatures and empirical evidences on innovative teaching, this study investigated the effects and causal relationships of technology-enabled metaliteracy with reasoning mapping (TMRM), pedagogical environment, and soft skills on students laboratory performance and achievement in biology. The study further probed direct and indirect relationships among the different endogenous and exogenous variables. The experiences of the students in the development of reasoning mapping were also contextualized. This study utilized a mixed method research design employing both quantitative and qualitative approaches. The study is mainly quasi-experimental however, part of the study also investigated any direct and indirect of various exogenous variables on the endogenous variables through a path analysis approach. The participants of this study were first-year students taking Bachelor of Science in Medical Technology (BSMT) at a private, non-sectarian, co-educational higher education institution in Manila. The study used the following research instruments: Computer-supported Collaborative Learning Scale (CSCL) and Social Reasoning Scale (SRS) for the soft skills, Conceptual-based Pedagogical Environment Inventory (CPEI) and Procedural-based Pedagogical Environment Inventory (PPEI) for the pedagogical environment, Laboratory Performance (LP), and Parasitology Achievement Test (PAT). In the qualitative part, a semi-structured interview question guide was used to contextualize students' experiences on the use of the Advanced Parasitology Pedagogical Package in the TMRM teaching approach. The results of the study showed that students exposed to TMRM teaching approach performed better and achieved higher composite mean posttest score than the students exposed to conventional teaching method (Non-TMRM) in terms of the Laboratory Performance (LP). Moreover, students exposed to TMRM teaching approach also performed better and achieved significantly higher mean posttest score than the students exposed to conventional teaching method (Non-TMRM) based on Parasitology Achievement Test. In terms of causal relationship, the initial model did not fit the different model fit indices and other diagnostic tests hence, a revised model was developed using the endogenous and exogenous variables. For both the TMRM and Non-TMRM teaching approaches, it was noted that laboratory performance is a predictor of students achievement using the revised model. Moreover, students perception of computer-supported collaborative and procedural-based pedagogical environment significantly and directly influenced students achievement in biology for the TMRM class only. The study also revealed that perceptions on conceptual-based learning indirectly influenced students achievement through its significant relations with laboratory performance. In terms of the qualitative data obtained through group and individual interviews, analysis of the students reflection, and the researchers observations and notes, there were phases with which the students were able to develop reasoning mapping of concepts, produced valid outputs, and eventually understood the cases and topics at hand. These phases include: reduction of the case, rounding up of information and events, revelation of initial framework, regulation of concepts and reasoning, resolution through redirection and realization of framework, refinement and re-creation of reasoning.